Improved health education for pregnant women in performing antenatal care in the COVID-19 pandemic - Lestari Sudaryanti; Amellia Mardhika; Arina Qona’ah; Anestasia Pangestu Mei Tyas; Muhammad Ardian Cahya Laksana (University of Merdeka Malang, 2021)
COVID-19 has been declared by WHO as a global pandemic. COVID-19 affects various lines of human life, especially the health aspect. East Java has ranked second in the COVID-19 cases in Indonesia. One of the efforts made to reduce the spread of COVID-19 is through clean and healthy activities and behaviors stay at home causes people to be limited in their activities except for very important purposes, especially activities for pregnant women. Pregnant women must and should carry out regular antenatal care checks. COVID-19 causes anxiety problems and worries for pregnant women to leave the house, including having pregnancy checks. But the mother is also worried about the condition and development of the fetus. This will increase the risk of maternal and infant mortality and the SDGs target in the third objective will not be met. This community service aims to provide knowledge related to antenatal care to high-risk using Poedji Rochyati Score Card (score 6-10) and very high-risk pregnant women (score 12) during the COVID-19 period. The method used in the implementation of this community service is material from resource persons, implementation of health education, and evaluation. The pregnant women were very enthusiastic about participating in this event, it was seen from the questions given to the team and vice versa. The results of the questionnaire show that there are differences in the level of knowledge of pregnant women for pre-test and post-test.